Premium Quality Rice (PQR) varieties BRRI Dhan 50 and BRRI Dhan 63 - CGIAR Research Program on Rice (2018)
The Premium Quality Rice (PQR) varieties BRRI Dhan 50 and BRRI Dhan 63, both of which were introduced and popularized with support from the Cereal Systems Initiative for South Asia (CSISA) in the project’s second and early third phase, were planted on over 29,000 hectares across Barisal, Faridpur and Jessore.